A theoretical study of spin-polarized transport properties of planar four-coordinate Fe complexes - Huang, Jing (2013)
We present a first-principles study of the spin-polarized transport properties of three planar four-coordinate Fe complexes with different noninnocent ligands sandwiched between two armchair (5,5) single-walled carbon nanotube (SWCNT) electrodes. Theoretical results clearly reveal that the current of the spin-up electrons through three examined molecular junctions is significant larger than that of the spin-down electrons. The low bias conductance is determined by the tail of transmission peak coming from the perturbed lowest unoccupied molecular orbital of the spin-up electrons. The high spin-filter efficiencies (up to 99.0%) are predicted for three planar four-coordinate Fe complexes coupled to SWCNTs.